2021
DOI: 10.3390/foods10040700
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Sicanaodorifera (Vell.) Naudin Epicarp as a Source of Bioactive Compounds: Chemical Characterization and Evaluation of Its Bioactive Properties

Abstract: Fruit bio-residues can be interesting for the recovery of bioactive molecules, such as phenolic compounds, tocopherols, vitamins, among others. These compounds can be targeted at the food industry and used for the development of functional foods or as food additives. In some cases, fruit epicarps are converted into by-products with non-commercial value, and generally, these fruit parts have a higher content in bioactive compounds than the fruit pulp. From this perspective, S. odorifera, a Brazilian fruit, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
5
13
0
1
Order By: Relevance
“…Studies on the red variety are more frequent than the black one. Most of the information available addresses the pulp, whereas some studies highlight the potential of the peel as a nutraceutical food and/or as a phytochemical source [5]. In fruits of the same genus Sicana from Amazonian forests, high pulp yields were reported, which were a good source of carbohydrates, vitamin A, and minerals such as zinc, Cu, Fe, and Mo [1].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the red variety are more frequent than the black one. Most of the information available addresses the pulp, whereas some studies highlight the potential of the peel as a nutraceutical food and/or as a phytochemical source [5]. In fruits of the same genus Sicana from Amazonian forests, high pulp yields were reported, which were a good source of carbohydrates, vitamin A, and minerals such as zinc, Cu, Fe, and Mo [1].…”
Section: Introductionmentioning
confidence: 99%
“…The quercetin aglycon was isolated and fully characterized from the Colombian S. odorifera seeds [ 14 ], in agreement with our results. Further, quercetin hexoside rhamnoside was informed in several studies addressing its peels extract [ 13 , 17 , 18 ] and it is found in the seeds of S. odorifera for the first time. Similarly, luteolin, quercetin dimethyl ether, and quercetin rhamnoside had not previously been reported in S. odorifera seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The aromatic spectrum of the pulp is characteristic and the compounds responsible for the flavor were described (94.8% free volatile; with 61.1% as aliphatic alcohols [ 16 ], whereas studies on the composition of the seeds and the bioactivity of its components are still scarce. The phytochemical profile of the pulp is promising as a source of antioxidant compounds [ 18 ]. Regarding the peels, flavonols and anthocyanins with antioxidant activity have been described [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, numerous studies have been reporting that a great variety of food wastes are rich sources of bioactive compounds, with great potential for recovery and application in food, cosmetic, and pharmaceutical industries [ 38 ]. Vitamin D 2 , e.g., was recovered from the biological surplus remaining from the mushroom cultivation industry [ 49 ]; phenolic acids and flavonoids were obtained from tomato crop remains (pruning and end-of-cycle plant materials) [ 50 ], and organic acids, phenolic compounds, and high concentrations of anthocyanins were extracted from Sicana odorifera fruit epicarp [ 30 ]. The recovery of value-added compounds from bioresidues and their applicability in food will be further discussed in topic 4.…”
Section: Value-added Compoundsmentioning
confidence: 99%